Formulation of Ketoprofen Transdermal Solid Dispersion Patch as an Analgesic and Anti-Inflammatory - Yani, Fitri; Arianto, Anayanti; Noersal, Rosidah (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: to formulate transdermal patches of ketoprofen solid dispersions, determine the effect of propylene glycol on the rate of release of ketoprofen transdermal solid dispersion patches to know the optimum transdermal patch form of a solid dispersion of ketoprofen could provided better analgesic and antiinflammatory effects compared to the trademark ketoprofen gel (Kaltrofen®). Design: this research was conducted using a transdermal experiment of dense solid dispersion patches of ketoprofen with variations in the amount of propylene glycol F1 (10%), F2 (20%) and F3(30%) , physicochemical characteristics (organoleptic, fiber, weight uniformity, folding enhancement and development), diffraction patterns (XRD), incompatibility patterns (FTIR), in vitro penetration testing. -vitro, evaluation of analgesic and anti-inflammatory activity. Interventions: the intervened variable were the in vitro penetration testing. In-vitro, evaluation of analgesic and anti-inflammatory effect of ketoprofen transdermal solid dispersion patch. Main outcome measures: the main measurement in this study were physicochemical characteristics (organoleptic, fiber, weight uniformity, folding enhancement and development), diffraction patterns (XRD), incompatibility patterns (FTIR), in vitro penetration testing. -vitro, evaluation of analgesic and anti-inflammatory activity. Results: transdermal patches of ketoprofen solid dispersion patches produce white, odorless preparations that have a flat surface, thickness between 0.0242 ± 0.0002 to 0.0269 ± 0.0003, weight uniformity 321.50 ± 0.78 to 381.54 ± 0.60, folding resistance between 375 ± 0.58 to 443 ± 1.53, all formulas already meet the requirements of physicochemical characteristics. F3 ketoprofen transdermal solid dispersion patch had a highest penetration degree and provide better analgesic effects compared to the trademark ketoprofen gel (Kaltrofen®), and there were significant differences between groups (p>0.05). Conclusion: it can be concluded that the use of 30% propylene glycol in F3 ketoprofen transdermal solid dispersion patch affects the rate of drug release and had a better anti-inflammatory effect compared to the trademark ketoprofen gel (Kaltrofen®).